Grazing exclusion reduced soil respiration but increased its temperature sensitivity in a Meadow Grassland on the Tibetan Plateau. Issue 3 (11th January 2016) - Chen, Ji; Zhou, Xuhui; Wang, Junfeng; Hruska, Tracy; Shi, Weiyu; Cao, Junji; Zhang, Baocheng; Xu, Gexi; Chen, Yizhao; Luo, Yiqi
Abstract: Understanding anthropogenic influences on soil respiration ( R s ) is critical for accurate predictions of soil carbon fluxes, but it is not known how R s responds to grazing exclusion (GE). Here, we conducted a manipulative experiment in a meadow grassland on the Tibetan Plateau to investigate the effects of GE on R s . The exclusion of livestock significantly increased soil moisture and above‐ground biomass, but it decreased soil temperature, microbial biomass carbon (MBC), and R s . Regression analysis indicated that the effects of GE on R s were mainly due to changes in soil temperature, soil moisture, and MBC. Compared with the grazed blocks, GE significantly decreased soil carbon release by 23.6% over the growing season and 21.4% annually, but it increased the temperature sensitivity (Q10 ) of R s by 6.5% and 14.2% for the growing season and annually respectively. Therefore, GE may reduce the release of soil carbon from the Tibetan Plateau, but under future climate warming scenarios, the increases in Q10 induced by GE could lead to increased carbon emissions. Abstract : Grazing exclusion decreased soil respiration. Grazing exclusion increased temperature sensitivity of soil respiration.